sqrt(b)*sqrt(c)*sqrt(d)*1/(sqrt(a)*6)=sqrt(a)*sqrt(c)*sqrt(d)*1/(sqrt(b)*18) 2*a+9*b+c/2+d/4=144

Дано

$$\frac{\sqrt{d} \sqrt{b} \sqrt{c}}{6 \sqrt{a}} = \frac{\sqrt{d} \sqrt{a} \sqrt{c}}{18 \sqrt{b}}$$

c d
2*a + 9*b + — + — = 144
2 4

$$\frac{d}{4} + \frac{c}{2} + 2 a + 9 b = 144$$
Ответ
$$a_{1} = — \frac{9 b}{2} — \frac{c}{4} + 72$$
=
$$- \frac{9 b}{2} — \frac{c}{4} + 72$$
=

72 — 0.25*c — 4.5*b

$$d_{1} = 0$$
=
$$0$$
=

$$c_{2} = 0$$
=
$$0$$
=

$$a_{2} = — \frac{9 b}{2} — \frac{d}{8} + 72$$
=
$$- \frac{9 b}{2} — \frac{d}{8} + 72$$
=

72 — 0.125*d — 4.5*b

$$b_{3} = — \frac{c}{30} — \frac{d}{60} + \frac{48}{5}$$
=
$$- \frac{c}{30} — \frac{d}{60} + \frac{48}{5}$$
=

9.6 — 0.0166666666666667*d — 0.0333333333333333*c

$$a_{3} = — \frac{c}{10} — \frac{d}{20} + \frac{144}{5}$$
=
$$- \frac{c}{10} — \frac{d}{20} + \frac{144}{5}$$
=

28.8 — 0.05*d — 0.1*c

1 Звезда2 Звезды3 Звезды4 Звезды5 Звезд (Пока оценок нет)
Загрузка...